Examining the Presence of Carbapenem-Resistant Enterobacterales and Routes of Transmission to Bovine Carcasses at Slaughterhouses - Uyanik, Tolga; Cadirci, Ozgur; Gucukoglu, Ali; Bolukbas, Aysegul (Elsevier, 2023)
This study was conducted to investigate the existence and possible transmission routes of CREs during the bovine slaughter process. A total of 600 samples including rectoanal mucosal swaps, bovine hides and carcasses were collected weekly, over a 20 week period from three different slaughterhouses in Samsun province and analyzed in terms of CRE. Isolation of CRE was performed using Chromatic CRE Agar. Obtained isolates were identified using PCR and VITEK MS. E-test method was used for screening of carbapenemase production and disk diffusion method was used for detection of phenotypic carbapenem resistance. Presence of five major carbapenemase genes were investigated by PCR and obtained amplicons were sequenced by Sanger sequencing. Clonal relatedness was investigated by Clermont phylo-typing and MLST. Plasmid incompability groups were determined by PCR-based replicon typing. Based on the results, only one bovine hide sample was found positive in terms of CRE and blaKPC-2 harbouring E. coli ST398 (phylogroup A) was identified. E. coli ST398 was found resistant to meropenem, imipenem, ertapenem, doripenem and also tested fluoroquinolones. ST398 was found to harbour three distinct replicons, namely N, FIIK, and FIB KQ. Inc. groups for these replicons were identified as IncN and IncFIIK. On the other hand, no concrete evidence has been obtained to suggest that CREs are spreading at the slaughterhouse level. Conclusively, conducting further studies in areas such as farms, pens, and feedlots is necessary to gain a better understanding of the transmission routes of CREs in livestock.
Çadirci, Özgür/0000-0003-2018-2545
Keywords: Carbapenem; Carcass; Enterobacterales; MLST; Plasmid; Slaughterhouse